Self-leadership to Innovation: The Role of Knowledge Sharing - Asbari, Masduki; Novitasari, Dewiana; Purwanto, Agus; Fahmi, Khaerul; Setiawan, Temmy (International Journal of Social and Management Studies, 2021)
This estudy einvestigates ethe eimpact eof eself-leaderships ewithin eemployees ein ethe emanufacturing eindustry ein eIndonesia etowards eemployee einnovation eand echecks eon ethe eimpact eof emediation efrom eknowledge esharing eto ethis erelationship. e125 eemployees ein ethe emanufacturing eindustry eparticipate ein ethis eresearch. eThe eresult eof eresearch eclaimed ethat eself-leadership ehas ea epositive eand esignificant eeffect eon eknowledge esharing eand eemployee einnovation. eLikewise, eknowledge esharing ehas ea epositive eand esignificant eeffect eon eemployee einnovation. eTherefore, ethe eresult eof ethe eresearch eshowed ethat eknowledge esharing ehas ea epartial emediation eimpact eon ethe erelationship ebetween eself-leadership eand eemployee einnovation